Some Thoughts on the Blood of Christ and Its Symbolism in Byzantine Epigrams Regarding the Cross And the Crucifixion - Kantaras, Anastasios (Sapiens ubique civis, 2023)
This study deals with the holy byzantine epigram regarding the Cross and the Crucifixion of Christ focusing on the presence, the position, and the importance of the blood of Christ on the instrument of torture that is the Cross. I will try to interpret and explain this repeated pattern through the lines of Byzantine epigrams, and, in the end, figure out any possible influences from other domains of Byzantine philology, such as hymnography and homilies, drawing further conclusions.